A case of alpha-fetoprotein-positive thymic small cell carcinoma: a case report - Masao Kobayashi; Soichiro Funaki; Eriko Fukui; Eiichi Morii; Yasushi Shintani (Surgical Case Reports, 2023)
Abstract Background An alpha-fetoprotein (AFP)-positive neuroendocrine tumor of the thymus is a rare thoracic malignancy. Few cases of AFP-positive thymic large cell neuroendocrine carcinoma have been reported, with no known previous report of an AFP-positive thymic small cell carcinoma. We encountered a patient with an AFP-positive small cell carcinoma and report here the clinical course. Case presentation A 40-year-old man was transferred to our hospital for a large anterior mediastinal tumor and showed an elevated serum AFP level. Computed tomography-guided biopsy results led to diagnosis of small cell carcinoma. Induction chemoradiotherapy was performed before surgery because of pulmonary artery invasion. The response to Induction chemoradiotherapy varied among sites, with the main tumor showing shrinkage and the metastasis site growth. This discrepancy suggested a histologic type unresponsive to or cancer cells potentially resistant to chemotherapy, thus a surgical re-biopsy was performed and histological findings revealed AFP-positive small cell carcinoma. Additional chemotherapy was performed, though could not control cancer progression, and the patient died 8 months after the first medical examination. Conclusions Our present clinical experience indicates the importance of histological examination for determining AFP-positive anterior mediastinal tumor treatment. Although AFP-positive neuroendocrine tumor of the thymus is relatively rarer than germ cell carcinoma, differential diagnosis with use of a histological examination should be considered because of the potentially poorer prognosis. The present clinical findings for an AFP-positive neuroendocrine tumor of the thymus case are considered useful for establishing an optimal treatment strategy in the future.